Management of status epilepticus: a narrative review. (10th January 2022) - Migdady, I.; Rosenthal, E. S.; Cock, H. R.
Summary: Status epilepticus causes prolonged or repetitive seizures that, if left untreated, can lead to neuronal injury, severe disability, coma and death in paediatric and adult populations. While convulsive status epilepticus can be diagnosed using clinical features alone, non‐convulsive status epilepticus requires confirmation by electroencephalogram. Early seizure control remains key in preventing the complications of status epilepticus. This is especially true for convulsive status epilepticus, which has stronger evidence supporting the benefit of treatment on outcomes. When status epilepticus becomes refractory, often due to gamma‐aminobutyric acid and N‐methyl‐D‐aspartate receptor modulation, anaesthetic drugs are needed to suppress seizure activity, of which there is limited evidence regarding the selection, dose or duration of their use. Seizure monitoring with electroencephalogram is often needed when patients do not return to baseline or during anaesthetic wean; however, it is resource‐intensive, costly, only available in highly specialised centres and has not been shown to improve functional outcomes. Thus, the treatment goals and aggressiveness of therapy remain under debate, especially for non‐convulsive status epilepticus, where prolonged therapeutic coma can lead to severe complications. This review presents an evidence‐based, clinically‐oriented and comprehensive review of status epilepticus and its definitions, aetiologies, treatments, outcomes and prognosis at different stages of the patient's journey.